Audit pricing and nature of controlling shareholders: Evidence from France - Chiraz Ben Ali; Cédric Lesage (China Journal of Accounting Research, 2013)
This study examines whether auditors are employed as a monitoring mechanism to mitigate agency problems arising from different types of controlling shareholders. In a context of concentrated ownership and poor investor protection, controlling shareholders can easily expropriate wealth from minority shareholders and profit from private benefits of control. However, this agency conflict has been rarely studied, as the most commonly assumed agency conflict occurs between managers and shareholders. Using an audit fee model derived from Simunic (1980), we study the impact of the nature of controlling shareholders on audit fees in French listed firms. Our results show: (1) a negative relationship between audit fees and government shareholdings; (2) a positive relationship between audit fees and institutional shareholdings; and (3) no relationship between audit fees and family shareholdings. These results illustrate the mixed effects of the nature of ownership on audit fees.
Keywords: G32; M42; 650; Audit fees; Controlling shareholder identity; Minority expropriation; Agency conflict